Students’ Perceptions on Using Quizizz Platform for Reading Comprehension of Recount Text of the Tenth Grade at Smkn 2 Kupang - Fenti Herodiana Lakapu; Novriani R. Manafe; Zantty O. Padahana (Indonesian Journal Publisher, 2026)
This research aimed to identify students’ perceptions and difficulties in using the Quizizz platform for reading comprehension of recount texts of the tenth-grade students of class X TKR 2 at SMKN 2 Kupang. This research used a descriptive qualitative method involving 26 students as participants. The data were collected through observation, questionnaires, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing and verification. The findings showed that students had positive perceptions toward the use of Quizizz in reading comprehension learning activities, as they felt interested, motivated, and actively participated in answering questions related to recount texts. However, students also showed negative perceptions, which were reflected in several difficulties, including limited vocabulary mastery, difficulty in understanding grammar, especially the simple past tense, dentifying the generic structure of recount texts, confusion in understanding Quizizz instructions, and technical problems such as unstable internet connections and device issues. These difficulties affected students’ ability to comprehend the recount texts, answer the questions correctly, and access the Quizizz platform smoothly. The findings indicate that Quizizz creates an interactive and engaging learning environment for reading comprehension; however, students still experience both learning-related and technical difficulties. Therefore, teachers are recommended to apply appropriate teaching strategies when using Quizizz in reading activities to help students overcome these difficulties while maintaining their motivation and engagement.